Knowledge, attitudes, and beliefs about acute coronary syndrome among patients with type 2 diabetes - Camille Alardis Hunte Johnson; Natássia Condilo Pitta; Carina Aparecida Marosti Dessotte; Rosana Aparecida Spadoti Dantas; Lídia Aparecida Rossi
Objective: to evaluate the knowledge, attitudes, and beliefs of Guyanese individuals with type 2 diabetes regarding acute coronary syndrome and explore associations between these measures and the population's sociodemographic and clinical characteristics. Method: cross-sectional study conducted in Linden, Guyana, with sixty type 2 diabetics, interviewed using a sociodemographic and clinical questionnaire and the Acute Coronary Syndrome-Response Index. The Mann-Whitney test was used to assess potential differences between groups according to the ACS-Response Index subscales, and sex, age, time since diabetes diagnosis, and body mass index and the Kruskal-Wallis test to compare the ACS-Response Index subscales according to educational level. Results: only two participants correctly answered more than 70% of the Knowledge subscale. Participants obtained low mean scores in all subscales. Less than half of the participants reported chest pain and arm pain as symptoms of heart attack. Significant differences were found when comparing Knowledge (p=0.008) and Attitudes (p=0.009) according to educational level. Conclusion: individuals with type 2 diabetes showed low level of Knowledge, Attitudes, and Beliefs. Participants who scored the highest in Knowledge and Attitudes presented the highest educational level. The results show a need for health professionals to heed knowledge deficits regarding acute coronary syndrome among type 2 diabetes.